'So you see, the story was not quite as you were told': Maleficent, Dance, Disney, and Cynicism as the Choreo-philosophical Critique of Neoliberal Precarity. (May 2017) - Hammond, Helena
Abstract : Dance bequeaths a conflicted legacy for resisting neoliberalism: the same portfolio careers; pick-up companies; and freelance working practices through which the artist-entrepreneur negotiates and survives the exigencies of the neoliberal market have themselves been co-opted by neoliberal economics as blueprints for labour practices in ways unimagined and never intended by arts practitioners. 'The freelancer' to quote Lauren Berlant (76) 'is one of the sovereign figures of neoliberalism'. 1 Looking beyond dance's unwitting complicity in the neoliberal contracting of the body, this paper focuses on dance as an emergent critical aesthetics that calls attention to the incorporation of the geopolitical by the post-statist neoliberal project. Its case study is Maleficent (2014 ), the Angelina Jolie popular cinema radical retelling, as prequel, of the back story of Sleeping Beauty's slighted fairy Carabosse. Maleficent's status as dance intertext is many-faceted: its titular character's conjunction of malevolence and magnificence and the sourcing of her predicament to an originating act of socio-economic disenfranchisement are familiar from the characterisation of Carabosse in Marius Petipa's choreography for the ballet The Sleeping Beauty (1890). Unspecified in the ballet, this act is elaborated in the film: 'the winged creature who rose to be protector of The Moors, a kingdom which needed neither king nor queen' to quote the film's narration, Maleficent is shorn of her wings in an act of land-grab motivated premeditated human interspecies violence. This act, betokening rape for Jolie, renders Maleficent's aerial choreographic spectacle pedestrianised; everyday and earthbound, just as Carabosse, denied vertiginous danse d'école vocabularies, must substitute more mundane mime in their place. This paper begins by establishing the strong bonds which bind Disney to dance; the extent to which, to quote Soviet avant-garde filmmaker Sergei Eisenstein, 'the art of animation…has its forerunner in ballet…At least in Fokine's ballets for Diaghilev…'. 2 Drawing on analyses of neoliberalism, those of David Harvey in particular, this paper then moves to consider Maleficent as the articulation of a critique of neoliberalism, one which – it will be suggested – relies heavily on Cynic philosophy for its formulation. Cynic philosophy, especially in the extended consideration of the Cynic life presented by Michel Foucault's final series of Collège de France lectures 3 will be critically important here. Arguing for Maleficent as the choreography of Feminist ethics in response to neoliberal policies that render human relations to the land ever more ethno-biologically precarious, this paper will point up the strong parallels that exist between the film and Cynic thinking. In Foucault's account, Cynicism especially prioritises the vie autre (other life). This makes Cynicism particularly effective as a vehicle for questioning neoliberal values and proposing others in their place. Maleficent's critique will be shown to be choreo -philosophical in the sense that it mobilises, and is highly reliant upon, a range of dance histories – those to do with The Sleeping Beauty especially – and dance practices, particularly those bound up, ultimately, with pantomime dance in Hellenistic ancient Greece. This article will suggest that pantomime dance as a close, cognate ally of Cynic philosophy, was already imbued, in some significant sense, with philosophical intent. It is pantomime dance's philosophical intent – this paper argues – that endures and is mobilised to such effect in the roles of Carabosse and Maleficent. Attention then turns to Alain Badiou's concept of cinema as philosophy. This article will suggest both that Badiou's concept is more indebted to dance than is generally acknowledged, and that it arguably strengthens the sorts of claims that can be made for Maleficent as choreo-philosophical critique. This paper also proposes, in a similar vein, that on the basis of his reading of Cynicism as actually highly motile, the late Foucault is more phenomenological in orientation and – so it would follow – less antithetical to dance and its study, than has hitherto been suggested.